1996
DOI: 10.1111/j.1540-8159.1996.tb03256.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Flutter: Lessons from Surgical Interventions (Musing on Atrial Flutter Mechanism)

Abstract: We report our experience with seven patients who underwent direct surgical ablation of problematic common flutter. Intraoperative mapping was obtained in four patients. Surgical techniques varied over time. A circular incision of the right atrium was performed in the first patient. Two patients had epicardial cryoablation of the isthmus between the inferior vena cava and the tricuspid valve annulus. Four patients had extensive endocardial cryoablation of the isthmus. There were no immediate postoperative compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Typical atrial flutter was initially surgically treated by Guiraudon et al using an ablation from the tricuspid valve to the inferior vena cava. 3 This lesion effectively interrupted the macro-reentrant circuit coursing up the atrial septum, down the atrial free wall, and through an area of slow conduction in the inferomedial atrial isthmus. Subsequently, the right atrial maze procedure was developed by Cox as part of the Cox-maze procedure for atrial fibrillation.…”
Section: Atrial Reentry Tachycardiamentioning
confidence: 99%
“…Typical atrial flutter was initially surgically treated by Guiraudon et al using an ablation from the tricuspid valve to the inferior vena cava. 3 This lesion effectively interrupted the macro-reentrant circuit coursing up the atrial septum, down the atrial free wall, and through an area of slow conduction in the inferomedial atrial isthmus. Subsequently, the right atrial maze procedure was developed by Cox as part of the Cox-maze procedure for atrial fibrillation.…”
Section: Atrial Reentry Tachycardiamentioning
confidence: 99%
“…Some of the early reports of modern cryothermal mapping were provided by the cardiac surgical experience with cryothermal energy [35]. Intraoperative cryoablation has been shown to be safe and effective and has been successfully used in humans to map or ablate the AV node [31], accessory pathways [36], AV nodal re-entrant tachycardia (AVNRT) [37], atrial flutter [38], and VT (in combination with subendocardial resection) [39][40][41].…”
Section: History Of Cryothermal Energymentioning
confidence: 99%
“…The train of knowledge elucidating the mechanisms of atrial flutter has proceeded down a more straightforward track. Although this arrhythmia, as seen in animal and interoperative mapping studies, has been shown to precede via a variety of different reentrant pathways, studies from a number of investigators more clearly established the importance of macroreentry around fixed or functional obstacles, 92 including the tricuspid valve as the site of reentry for isthmus dependent and atypical flutters 93 . In the former case, propagation via the cavotricuspid isthmus has been critical as a central corridor of activation around the tricuspid valve.…”
Section: Elucidation Of Microreentrant Arrhythmiasmentioning
confidence: 99%